Electron-deficient acene-based liquid crystals: dialkoxydicyanopyrazinoquinoxalines1. Issue 13 (7th April 2015) - Takeda, Takashi; Tsutsumi, Jun'ya; Hasegawa, Tatsuo; Noro, Shin-ichiro; Nakamura, Takayoshi; Akutagawa, Tomoyuki
<x xml:space="preserve">Abstract</x> Dialkoxydicyanopyrazinoquinoxaline exhibited liquid crystallinity, which was cooperatively stabilized by three noncovalent interactions, i.e. hydrophobic interaction, dipole–dipole interaction and π–π interaction.